2011
DOI: 10.1103/physrevb.84.035126
|View full text |Cite
|
Sign up to set email alerts
|

Variational discrete variable representation for excitons on a lattice

Abstract: We construct numerical basis function sets on a lattice, whose spatial extension is scalable from single lattice sites to the continuum limit.They allow us to compute small and large bound states with comparable, moderate effort. Adopting concepts of discrete variable representations, a diagonal form of the potential term is achieved through a unitary transformation to Gaussian quadrature points. Thereby the computational effort in three dimensions scales as the fourth instead of the sixth power of the number … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The binding energies of the yellow and green paraexcitons are approximately equal [19] and hence do not appear in Eq. (A2) explicitly.…”
Section: Appendix A: Exciton States and Strainmentioning
confidence: 99%
“…The binding energies of the yellow and green paraexcitons are approximately equal [19] and hence do not appear in Eq. (A2) explicitly.…”
Section: Appendix A: Exciton States and Strainmentioning
confidence: 99%
“…This prevents the use of direct solvers such as PARDISO [22] or ILUPACK [23], which have been used successfully for, e.g., Anderson localization [21]. In some applications the matrix is not even stored explicitly but constructed 'on-thefly' [24,25]. Therefore, we assume that the only feasible sparse matrix operation in ChebFD is sparse matrix vector multiplication (spMVM).…”
Section: Introductionmentioning
confidence: 99%
“…14 Also, a computational study, which requires the electron and hole effective masses as known parameters, has shown that the central-cell corrections account for the large excitonic mass. 15 Since the excitonic mass is a key parameter determining the critical temperature for a quantum phase transition, such as Bose-Einstein condensation, solving the controversy on the hole effective mass is important.…”
Section: Introductionmentioning
confidence: 99%